Practice of preoperative assessment by anaesthetists. Issue 6492 (10th August 1985) - Curran, J; Chmielewski, A T; White, J B; Jennings, A M
Abstract : The practice of preoperative assessment in 24 departments of anaesthesia in Great Britain and Ireland was surveyed. Most departments had no rigid policies governing assessment, and many served several hospitals. There was little evidence that admission procedures of patients scheduled for surgery or the organisation of operating lists took account of the problems encountered by anaesthetists undertaking preoperative assessment. From the participating departments 415 anaesthetists completed a questionnaire of their individual practice. Most (57%) visited at least 80% of their patients preoperatively, but 22% saw less than 50% of patients. The detection of potential anaesthetic problems and the establishment of rapport with patients were highly rated reasons for conducting such visits. Failure to visit was often related to organisational defects within the hospital service, and anaesthetists saw little prospect of improving these defects. The demands created by the needs of preoperative assessment on the one hand, and the need for a rapid turnover of surgical patients and financial stringency on the other, conflict, and this conflict is not easily reconciled.